Improving High School and Vocational School Teachers in Writing Skill - Surya, Awang; Azharul, Firmansyah; Wilarso, W.; Idris, Mustopa; Azziqi, Yusril Zindar; Retno, Iwung Hari (Jurnal Dedikasi, 2020)
Sekolah Tinggi Teknologi Muhammadiyah Cileungsi has the duty of the College Dharma Chess which includes education and teaching activities, research and community service, and AIKA and Al-Islam. The purpose of this research is to teach writing methods to teachers, to facilitate teaching and learning. The method used in this research are identification of the problem, conduct a field survey, finding material, and direct training Â to representatives of each high school / vocational school teachers. In this training participants were given the easiest writing method. From telling great writers in life in the world, where they can exist in writing. Then the participants were asked to write an article to get used to writing. After the end of the activity, participants are asked to share in the group or discuss directly with the speaker, so that the writing that has been made can be immediately reviewed. Solutions in writing training, taking the time to write, and frequent discussions with people who often write. The result of this research is the teachers know writing techniques to develop teaching activity in the classroom.